Chasing beauty : the life of Isabella Stewart Gardner - Dykstra, Natalie (Mariner Books, 2024)
Chronicles the life of the creator of one of America's most stunning museums-an American original whose own life was remade by art; includes archival photos of her world, museum and the art she collected.